2005
DOI: 10.1002/mds.20508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repetitive TMS and fluoxetine on cognitive function in patients with Parkinson's disease and concurrent depression

Abstract: Previous studies show that cognitive functions are more impaired in patients with Parkinson's disease (PD) and depression than in nondepressed PD patients. We compared the cognitive effects of two types of antidepressant treatments in PD patients: fluoxetine (20 mg/day) versus repetitive transcranial magnetic stimulation (rTMS, 15 Hz, 110% above motor threshold, 10 daily sessions) of the left dorsolateral prefrontal cortex. Twenty-five patients with PD and depression were randomly assigned either to Group 1 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(131 citation statements)
references
References 36 publications
6
117
2
6
Order By: Relevance
“…Despite mixed results for healthy participants, a number of promising rTMS studies have shown beneficial WM effects in neuropsychiatric patients, both for depression (O'Connor et al 2003;Fabre et al 2004;Hausmann et al 2004;Schulze-Rauschenbach et al 2005;Boggio et al 2005;Kuroda et al 2006;Bloch et al 2008;Vanderhasselt et al 2009;Guse et al 2010) and schizophrenia (Demirtas-Tatlidede et al 2013;Levkovitz et al 2011;Barr et al 2013). Compromised cortical activity of neuropsychiatric patients, associated with hypo-dopaminergic states (Stahl 2013) and neurophysiological inhibitory deficits (Radhu et al 2013), may explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Despite mixed results for healthy participants, a number of promising rTMS studies have shown beneficial WM effects in neuropsychiatric patients, both for depression (O'Connor et al 2003;Fabre et al 2004;Hausmann et al 2004;Schulze-Rauschenbach et al 2005;Boggio et al 2005;Kuroda et al 2006;Bloch et al 2008;Vanderhasselt et al 2009;Guse et al 2010) and schizophrenia (Demirtas-Tatlidede et al 2013;Levkovitz et al 2011;Barr et al 2013). Compromised cortical activity of neuropsychiatric patients, associated with hypo-dopaminergic states (Stahl 2013) and neurophysiological inhibitory deficits (Radhu et al 2013), may explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Fregni et al 161 found that high-frequency rTMS applied over the left DLPFC daily for ten days resulted in reduction of depressive symptoms. Boggio et al 162 found that this improvement extended to cognitive functions such as verbal fluency and executive functions. The same authors found that anodal tDCS (2 mA) applied over the left DLPFC of patients with Parkinson's disease resulted in an improvement in working memory task 163 .…”
Section: Mdd and Cognitionmentioning
confidence: 96%
“…64 Indeed, anodal tDCS over the left DLPFC with the cathode over the right supraorbital region has been shown to improve working memory in healthy subjects, 65 as well as improve mood in patients with major depression. 66,67 In this context, several studies have documented the beneficial effects of TMS on cognitive symptoms in PD 68,69 without worsening motor symptoms. 70 These results support the idea that active stimulation of the DLPFC with tDCS could also have beneficial effects on both affective and cognitive domains in patients with PD.…”
Section: Tdcs For Cognitionmentioning
confidence: 99%